SUITABILITY OF DURUM WHEAT VARIETIES FOR THE PRODUCTION OF DOUGHNUTS - Rehman, Salim-ur-; Azam, Muhammad; Hussain, Sarfraz; Shahzadi, Naureen (Biological Sciences - PJSIR, 2004)
Two durum wheat varieties D-97 and WDK-85 and one bread wheat variety Inqlab-91 were tested to assess the suitability for the production of doughnuts. Doughnuts are fermented bakery products, fried in hot oil/fat to form sweet snacks. Doughnuts of good quality has a dry crust and are crispy. The chemical characteristics of wheat grains such as moisture, ash, protein, fat and fiber contents varied from 8.90 to 9.45%, 1.40 to 1.55%, 11.50 to 12.25%, 1.14 to 1.81% and 2.32 to 2.73%, whereas, the chemical characteristics of patent flours varied from 13.31 to 14.95%, 0.35 to 0.54%, 11.02 to 11.81%, 0.57 to 0.96% and 0.36 to 0.41%, respectively. The interactions were found to be highly significant in case of crumb and overall acceptability. Thus, it is concluded that doughnuts made from D-97 are more acceptable to the consu- mers as they obtained maximum score followed by Inqlab-91. Therefore, this study indicated that good quality doughnuts could be prepared from durum wheat varieties.